Burden of itch in epidermolysis bullosa. (22nd June 2014) - Snauwaert, J.J.L.; Yuen, W.Y.; Jonkman, M.F.; Moons, P.; Naulaers, G.; Morren, M.A.
<x xml:space="preserve">Abstract</x> What's already known about this topic? In a prior study, itch was the most troublesome problem in children with epidermolysis bullosa (EB), and even more important than pain and integration problems. What does this study add? In this study the extent and characteristics of itch were measured in the three major EB subtypes. We compared itch in EB and atopic dermatitis.